2020
DOI: 10.3390/genes11091000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Pine Trees Treated with Resistance-Inducing Substances against the Nematode Bursaphelenchus xylophilus

Abstract: The pinewood nematode (PWN) Bursaphelenchus xylophilus causes pine wilt disease, which results in substantial economic and environmental losses across pine forests worldwide. Although systemic acquired resistance (SAR) is effective in controlling PWN, the detailed mechanisms underlying the resistance to PWN are unclear. Here, we treated pine samples with two SAR elicitors, acibenzolar-S-methyl (ASM) and methyl salicylic acid (MeSA) and constructed an in vivo transcriptome of PWN-infected pines under SAR condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Flavonoids play a key role in tree defense against the PWN through signal transduction and metabolic regulation (Isshiki et al, 2014; Vazquez-Vilar et al, 2023; Wang et al, 2024a). Following PWN invasion, the host recognizes PWN secretions and related microbial products, activates defense signaling pathways, and induces the expression of flavonoids (Park et al, 2020). These substances have antioxidant and antimicrobial functions that limit PWN pathogenicity and microbial infection (Raorane et al, 2019; Liu et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids play a key role in tree defense against the PWN through signal transduction and metabolic regulation (Isshiki et al, 2014; Vazquez-Vilar et al, 2023; Wang et al, 2024a). Following PWN invasion, the host recognizes PWN secretions and related microbial products, activates defense signaling pathways, and induces the expression of flavonoids (Park et al, 2020). These substances have antioxidant and antimicrobial functions that limit PWN pathogenicity and microbial infection (Raorane et al, 2019; Liu et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported genome-wide analyses of pine trees treated with MeSA against the nematode B. xylophilus ( Park et al, 2020 ). The application of the MeSA, effective in terms of reducing PWD severity, mainly induce genes involved in systems for protection from ROS damage as well as genes encoding flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MeSA can effectively control PWD by inducing flavonoid biosynthesis through comparative in vivo transcriptomics on pine seedlings ( Park et al, 2020 ). However, the establishment of optimal treatment conditions for high efficiency of MeSA and application to the field have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The application of MeSA in P. densiflora and P. thunbergii seedling leaves in the form of spray one and two weeks before PWN inoculation significantly decreased disease progression when compared to seedlings without treatment [ 119 , 120 , 124 ]. Treatment of P. densiflora plants with MeSA and subsequent inoculation with PWN seem to induce genes and pathways similar to those previously associated with PWN resistance, such as PR-1 , PR-2 , PR-5 , peroxidases, extensins, flavonoid biosynthesis genes, and genes involved in ROS detoxification [ 119 , 124 ]. The expression levels of these genes were much higher in plants treated with MeSA than in non-treated plants, reinforcing their importance in achieving resistance to PWD.…”
Section: Defense Response Induced By the Application Of Phytohormones...mentioning
confidence: 99%
“…On the other hand, the trunk injection of MeJA had a small effect on improving P. densiflora resistance to PWN [ 124 ]. However, spraying P. massoniana seedlings with MeJA seems to induce the production of diterpenes and deter the insect vector Monochamus alternatus from feeding on the stems of elicited plants [ 125 ].…”
Section: Defense Response Induced By the Application Of Phytohormones...mentioning
confidence: 99%